Introduction: Mise en abyme. Issue 2 (1st September 2020) - Grove, Laurence; Magnussen, Anne; Miller, Ann
Abstract : This edition of European Comic Art was not planned as a themed issue, but during the editing process, we noted that all four articles may be regarded as offering variations on mise en abyme, the use of an image within an image or text within a text, whereby the inner picture or story illuminates the outer work. This is a term whose heraldic origins link it to visual depictions, and a figure that the comics medium, with its single and multiple frames, can deploy to particular effect. We will show in our conclusion how the frame within a frame occurs in the articles introduced below, either literally or metaphorically.